Phantom trips: Overestimating the traffic impacts of new development - Millard-Ball, Adam (Journal of Transport and Land Use, 2015)
The Trip Generation Manual is the standard reference for assessing the impacts of new development on traffic congestion and the environment in the United States. However, a comparison to household surveys suggests that the Trip Generation Manual overestimates trips by 55 percent—likely because its data represent a biased sample of development in the U.S. Moreover, the data in the Trip Generation Manual are ill suited to many analyses of traffic impacts, development impact fees, and greenhouse gas emissions because they do not account for substitution effects. Most trips “generated” by new developments are not new, but instead involve households reshuffling trips from other destinations. These twin problems—theoretical and practical—are likely to lead to the construction of excessive roadway infrastructure and to the overestimation of the congestion, fiscal, and environmental impacts of new development.